Intestinal stem cell function in Drosophila and mice - Jiang, Huaqi; Edgar, Bruce (Current opinion in genetics & development, 2012)
Epithelial cells of the digestive tracts of most animals are short-lived, and are constantly replenished by the progeny of long-lived, resident intestinal stem cells. Proper regulation of intestinal stem cell maintenance, proliferation and differentiation is critical for maintaining gut homeostasis. Here we review recent genetic studies of stem cell-mediated homeostatic growth in the Drosophila midgut and the mouse small intestine, highlighting similarities and differences in the mechanisms that control stem cell proliferation and differentiation.